IMPLEMENTASI DISCOVERY LEARNING DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN PEMAHAMAN KESEIMBANGAN EKOSISTEM PADA SISWA KELAS V SDN 1 RULUNG MULYA - Resty Setyoningsih Misyati; Kms.Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and implement a Discovery Learning model on the topic of Ecosystem Balance in the fifth grade at SD Negeri 1. The implementation procedure covers six stages: providing stimulation, identifying problems, data collection, information processing, verification, and generalization. The learning was conducted for 3 sessions (105 minutes) involving 14 students. The results showed a significant increase in student learning activity, understanding of ecosystem balance concepts, and environmental awareness. The average learning outcome reached 85.7 with a classical completeness of 92.8%. The challenges faced included limited group discussion time and difficulties for some students in analyzing cause-and-effect relationships, which were addressed through intensive guidance and the use of interactive visual media. The conclusion of this study is that the Discovery Learning model is effective in enhancing students' conceptual understanding and critical thinking skills on ecosystem material. Follow-up in the form of applying this model to other IPAS topics with additional time for deeper exploration.